(untitled) (CAHIERS MAGELLANES-NS, 2024)
among those who are at risk of developing the stated conditions. Concerning awareness and Knowledgescore of emergency ophthalmic diseases, a significant proportion of the population, 93.0% to be precise,falls under the category of having a poor level of awareness and knowledge regarding emergencyophthalmic diseases. Only a small percentage of respondents, 1.8% demonstrated a good level ofawareness and knowledge, while 5.3% exhibited a moderate level. In contrast, 60.4% of the respondentshave heard about retinal detachment, indicating a considerable level of awareness in the population.Moreover, there was a statistically significant relation to being a healthcare worker (p value=0.0001),but there was a statistically insignificant relation to age, region, gender, household income and theduration since last eye examination among the participants.Conclusion: Based on our study outcome, both knowledge and awareness of the eye emergencies arelow among the population. However, there was a considerable level of awareness in the population asregard retinal detachment. Thus, to ameliorate awareness and knowledge, there is a need for publichealth education of ophthalmic emergencies. Teaching the public about both the risk factors andsymptoms will lead to early recognition of the diseases and, thus, prevention.